2015
DOI: 10.12659/msm.893610
|View full text |Cite
|
Sign up to set email alerts
|

Expression Level of Genes Coding for Cell Adhesion Molecules of Cadherin Group in Colorectal Cancer Patients

Abstract: BackgroundColorectal Cancer (CRC) is one of the most frequently diagnosed neoplasms and also one of the main death causes. Cell adhesion molecules are taking part in specific junctions, contributing to tissue integrality. Lower expression of the cadherins may be correlated with poorer differentiation of the CRC, and its more aggressive phenotype. The aim of the study is to designate the cadherin genes potentially useful for the diagnostics, prognostics, and the treatment of CRC.Material/MethodSpecimens were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…MMP28, as in the case of MMP9, is associated with the activity of the cadherin group, which is the major mediator of cell adhesion. This relationship is very complex in CRC, which results from the changeable activity of genes encoding these mediators [34]. Xiao et al [35] demonstrated that miRNA-144 (suppressed by the expression of GSPT1) may be the connecting element to regulate the expression of Survivin, thereby inhibiting MMP28.…”
Section: Discussionmentioning
confidence: 99%
“…MMP28, as in the case of MMP9, is associated with the activity of the cadherin group, which is the major mediator of cell adhesion. This relationship is very complex in CRC, which results from the changeable activity of genes encoding these mediators [34]. Xiao et al [35] demonstrated that miRNA-144 (suppressed by the expression of GSPT1) may be the connecting element to regulate the expression of Survivin, thereby inhibiting MMP28.…”
Section: Discussionmentioning
confidence: 99%